Rail trails and housing values: A longitudinal study - Gross, Alina; Bristow , Robert S. (Turyzm/Tourism, 2022)
Greenways are recognized as an essential tool to build sustainable communities. An example in the United States are the rail trails where decommissioned rail corridors are being improved to provide the benefits of non-motorized transportation systems for recreation and exercise, and the daily commute to school, work and shopping. Yet despite these benefits some still argue the presence of the rail trail as a NIMBY (Not In My Back Yard). To address this argument, we calculate the economic benefit to homeowners living in proximity to rail trails over a ten year period to observe the dramatic changes in value over time. It was hypothesized that there would be a change in housing values based on proximity to greenways. This article will begin with an overview and a literature review on research related to greenways and home values, describe the context of this particular case study in the Pioneer Valley of Western Massachusetts, United States, provide an overview of the methods employed for the calculations and analysis, and conclude with some reflections and the potential limitations that should be considered for undertaking future research on this topic.